The Effects of Augmented Reality Applications on Secondary Students' Academic Achievement in Science Course - Tarık Talan; Zeynel Abidin Yilmaz; Veli Batdi (Journal of Education in Science, Environment and Health)
The aim of this study is to investigate how the use of augmented reality (AR) applications in educational environments affects students’ achievement levels. The study was carried out through two dimensions; a quantitative and a qualitative aspect. The study was conducted with 7th-grade students in a public secondary school in Turkey as part of a science course. For this purpose, AR applications and activities were implemented that were suitable for the topic of Astronomy. The quasi-experimental model and one of the quantitative research methods were used for the study. As data collection instruments an achievement test and an interview form were made use of. AR activities were used for teaching in the experimental group, while the traditional method for the control group. The quantitative results of the study showed that there was a significant difference in the achievement level of learners in favor of the experimental group. The interviews with the students revealed that the AR applications used in the course were interesting, that they increased interest, desire, and motivation in class, and that they facilitated learning. However, students indicated that the cost of the AR materials was high, that they had difficulty in obtaining the materials, and that they sometimes had technical problems. Another limitation was expressed as that the excess the number of students makes it more difficult to take the advantage of AR activities. Students suggested that lowering the cost of AR materials and using them in other lessons can be more effective in learning environment.